2020
DOI: 10.2147/opth.s271789
|View full text |Cite
|
Sign up to set email alerts
|

<p>Short-Term Efficacy and Safety of Omidenepag Isopropyl in Patients with Normal-Tension Glaucoma</p>

Abstract: To retrospectively evaluate the short-term efficacy of omidenepag isopropyl (EYBELIS 0.002%) by assessing its intraocular pressure (IOP)-lowering capability and safety in patients with normal-tension glaucoma (NTG). Patients and Methods: Fifty-four NTG patients (54 eyes) who were newly administrated with omidenepag isopropyl were enrolled in the study. The subjects comprised 22 men and 32 women, and the mean age of the subjects was 55.0 ± 14.1 years. The mean deviation value using the Humphrey visual field tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…OMDI has better safety than latanoprost ( Aihara et al, 2019 ). The ocular AEs induced by OMDI is mild or moderate, and the most frequently reported are conjunctival hyperemia, photophobia, and eye pain ( Aihara et al, 2020a ; Inoue et al, 2020a ; Aihara et al, 2020b ). Conjunctival hyperemia is dose-dependent ( Aihara et al, 2019 ), and most frequently observed in small vessels (51%) in OMDI-treated eyes, and in both large and small vessels (81%) in ripasudil-treated eyes ( Terao et al, 2020 ).…”
Section: Topical Monotherapy Agentsmentioning
confidence: 99%
“…OMDI has better safety than latanoprost ( Aihara et al, 2019 ). The ocular AEs induced by OMDI is mild or moderate, and the most frequently reported are conjunctival hyperemia, photophobia, and eye pain ( Aihara et al, 2020a ; Inoue et al, 2020a ; Aihara et al, 2020b ). Conjunctival hyperemia is dose-dependent ( Aihara et al, 2019 ), and most frequently observed in small vessels (51%) in OMDI-treated eyes, and in both large and small vessels (81%) in ripasudil-treated eyes ( Terao et al, 2020 ).…”
Section: Topical Monotherapy Agentsmentioning
confidence: 99%
“…Omidenepag isopropyl (OMDI) was launched in Japan in 2018 as the first EP 2 receptor agonist to obtain regulatory approval for the treatment of glaucoma and ocular hypertension. OMDI exhibited an IOP-lowering effect that was not inferior to the FP receptor agonist latanoprost, without producing prostaglandinassociated periorbitopathy (PAP) which adversely affects adherence to therapy [6][7][8][9][10]. On the other hand, since OMDI caused rare but serious adverse events such as cystoid macular edema (CME) and decreased visual acuity in a previous study [11], further information on safety under clinical use is required.…”
Section: Introductionmentioning
confidence: 99%
“…However, adverse drug reactions, including conjunctival hyperaemia and eye pain, occurred in 7.4%. 127 This drug has not yet been approved for use in pseudophakic patients, because of the risk of cystoid macular edema. Further studies are needed.…”
Section: Updates In Treatment: Surgical Interventions Lasers and Newe...mentioning
confidence: 99%